Integrative cardiology - Devries, Stephen R.; Dalen, James E., 1932- (Weil integrative medicine library., 2011)
Integrative Cardiology is an exploration of a new and much-needed perspective in cardiac care: the intelligent synthesis of conventional medicine with alternative approaches not typically part of Western medical curriculum. More than a blending of two approaches, this new perspective in cardiology highlights specific gaps in conventional heart care, and examines how alternative approaches may be ideally suited to address these missed opportunities. Cardiology is an ideal specialty for an integrative approach. Heart disease is largely preventable. The influence of nutrition, physical activity.